2022
DOI: 10.1097/pas.0000000000002011
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Diagnosis of Epstein-Barr Virus-positive Inflammatory Follicular Dendritic Cell Sarcoma

Abstract: Epstein-Barr virus (EBV)-positive inflammatory follicular dendritic cell (FDC) sarcoma (EBV+ IFDCS) is a rare entity, and its histopathological characteristics have not been fully described. Here, we investigated the wide morphologic spectrum and immunophenotype of this tumor with the aim to help avoid misdiagnosis. Thirteen cases of EBV+ IFDCS were retrospectively analyzed, combined with a review of 70 cases reported in the literature. The median age of patients was 49 (range, 29 to 67 y). Six patients were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Goh et al [6]reports a case of colon EBV + in ammatory FDC sarcoma with obviously increased IgG4 + plasma cell in ltration, and without other pathological features of IgG4 related diseases, such as vasculitis obliterans and sclerotic stroma. Other studies have covered that several cases of EBV + in ammatory FDC sarcoma occurring in liver and spleen have a well IgG4 expression, satisfying the pathological criteria of IgG4 related disease, but lacking other evidence of IgG4 related diseases [12,13]. In our case, IgG and IgG4 staining were performed, with only a very small amount of IgG4-positive plasma cells were seen.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Goh et al [6]reports a case of colon EBV + in ammatory FDC sarcoma with obviously increased IgG4 + plasma cell in ltration, and without other pathological features of IgG4 related diseases, such as vasculitis obliterans and sclerotic stroma. Other studies have covered that several cases of EBV + in ammatory FDC sarcoma occurring in liver and spleen have a well IgG4 expression, satisfying the pathological criteria of IgG4 related disease, but lacking other evidence of IgG4 related diseases [12,13]. In our case, IgG and IgG4 staining were performed, with only a very small amount of IgG4-positive plasma cells were seen.…”
Section: Discussionsupporting
confidence: 47%
“…At present, there are few studies on molecular changes related to FDC sarcoma. It has been reported that clonal IGH (± IGK) gene rearrangements can occur in classical FDC sarcoma [12,13], suggesting that a subset of FDC sarcoma may inherited B-lymphocyte genotypes and derives from committed B-cell progenitors. As to EBV + in ammatory FDC sarcoma, molecular researches are even less.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with conventional type, it is more common in women and usually an isolated disease with a better prognosis. EBER positivity is an important clue for the diagnosis of the tumor ( 11 ). Our patient presented with multiple lymphadenopathy throughout the body; histology showed that the tumor cells were abundant, and there were obvious atypia, numerous mitoses, and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells typically exhibit immunophenotypic characteristics of FDCs, such as the expression of CD21, CD23, CD35, D2-40, EGFR, and CXCL13. However, they may also exhibit myoid cell differentiation ( 5 ). A notable histological distinction from FDCS is the presence of a prominent reactive lymphoplasmacytic infiltrate, consisting of mixed B and T cells ( 1 , 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%